Alternative Indias : writing, nation and communalism - Morey, Peter; Tickell, Alex. (Amsterdam ; New York : Rodopi, 2005)
The debate over whether religious or secular identities provide the most viable model for a wider national identity has been a continuous feature of Indian politics from the late nineteenth century to the present day. Moreover, in the last thirty years the increasingly communal articulation of popular politics and the gradual rise of a constellation of Hindu nationalist parties headed by the BJP has increased the urgency of this debate. While Indian writing in English has fostered a long tradition of political dissent, and has repeatedly questioned ethnocentric, culturally exclusive forms of p.
The Routes of National Identity in Amitav Ghosh's The Shadow LinesInscribing a Sikh India: An Alternative Reading of Khushwant Singh's Train to Pakistan; No Passports, No Visas: The Line of Control Between India and Pakistan in Contemporary Bombay Cinema; Afterword; Contributors; Index.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Nationalism in literature; Communalism in literature; Writing in literature; Religion and literature -- India; Nationalisme dans la littérature.; Communalisme dans la littérature.; Écriture dans la littérature.; Religion et littérature -- Inde; TRAVEL -- Special Interest -- Literary; LITERARY CRITICISM -- General; Communalism in literature; Nationalism in literature; Religion and literature; Writing in literature; India; Electronic book